2022
DOI: 10.1155/2022/5396393
|View full text |Cite|
|
Sign up to set email alerts
|

Reform of PBL Teaching Mode of Microcomputer System and Embedded Application Course Group

Abstract: In recent years, the problem-based learning (PBL) model has become a hot spot in the education field. Its unique “learner”-centered and “problem-based” characteristics have been widely used in teaching. Make a useful attempt to comply with the development of the times and the requirements of education. This article puts forward the research on the reform of PBL teaching mode based on the microcomputer system and embedded application course group, using literature data method, fuzzy comprehensive analysis metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Problem-based Learning (PBL) is a teaching method in which the teacher throws out the problem, the students solve the problem according to their own thinking, and the teacher guides the students appropriately according to their progress in solving the problem. It emphasizes the students' in-depth understanding of the knowledge and its practical application, and focuses on cultivating the students' hands-on ability, design ability, and innovative spirit [7][8][9][10].…”
Section: Teaching Methodsmentioning
confidence: 99%
“…Problem-based Learning (PBL) is a teaching method in which the teacher throws out the problem, the students solve the problem according to their own thinking, and the teacher guides the students appropriately according to their progress in solving the problem. It emphasizes the students' in-depth understanding of the knowledge and its practical application, and focuses on cultivating the students' hands-on ability, design ability, and innovative spirit [7][8][9][10].…”
Section: Teaching Methodsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%